Analisis "Bangga menjadi Anak Indonesia" untuk Siswa Kelas VI Berbasis Kelayakan Buku BSNP - Agustina You; Panca Dewi Purwati; Aradisa Zahra Rachma; Ithma Anna Rosada; Nurullita Riski Ardiyanti; Radinda Datya Yosi Faratifa (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Indonesian language textbooks play an important role in shaping character and national identity starting from the elementary school level. One crucial aspect of teaching materials is linguistic feasibility, which includes grammar, vocabulary, and sentence structure that are appropriate to the cognitive development of students. The objectives of this research activity are: (1) to describe the results of content analysis, (2) to describe the results of language analysis, (3) to describe the results of presentation analysis, and (4) to describe the results of graphical analysis in chapter 1 of the Indonesian language textbook for grade 6 published by the Ministry of Education, Culture, Research, and Technology in 2022. This research uses a qualitative approach with content analysis methods. The focus of the analysis includes morphology, syntax, and the appropriateness of vocabulary for students aged 11–12 years. Data were analyzed based on language feasibility indicators according to the National Education Standards Agency (BSNP), such as grammatical accuracy, spelling consistency, and text readability. The results of the study show that (1) content feasibility is in accordance with the elements and learning achievements as well as the actualization of material relevant to the context of students; (2) language feasibility is considered sufficiently clear, but deficiencies were found in spelling (60%), sentence structure (40%), as well as the use of foreign terms and reduplication; (3) presentation feasibility is considered less systematic, with an imbalance between topics and a lack of practice questions; and (4) graphical feasibility shows good typography and layout, but there are few illustrations and a lack of attractive visual variation. The conclusion of this study is that the book is suitable for use as teaching material with several recommended improvements in the linguistic aspect to increase the effectiveness of learning. Suggested improvements include simplifying sentences, adding a glossary, and increasing language consistency so that the textbook becomes more communicative and easier to understand.